Additive for lithium ion battery and application thereof
By using additives containing specific polymers and stabilizers in lithium-ion batteries, the problem of easy dispersion of thick electrodes and cathode particles is solved, good dispersion of conductive agents and high solids content and stability of cathode slurry materials are achieved, and the mechanical and electrochemical properties of the battery are improved.
Patent Information
- Application Number
- CN202510092089.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-21
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing lithium-ion battery thick electrodes are prone to lobes and the nano-killed positive electrode particles are difficult to disperse.
An additive containing polymers such as ethyl cellulose, polyvinylpyrrolidone and hydrazine-based compounds is used as a dispersant for the conductive agent to improve the dispersion performance of the conductive agent, and to improve the solid content and viscosity stability during the positive electrode slurry combination process.
Significantly improve the dispersion performance of the conductive agent, reduce the resistivity, improve the solid content and viscosity stability of the positive electrode slurry material, prevent electrode cracking, and improve mechanical properties and coating uniformity.
Smart Images

Figure BDA0005251857260000011 
Figure BDA0005251857260000021 
Figure BDA0005251857260000022
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium ion batteries, and in particular to an additive for lithium ion batteries and an application thereof. Background Art
[0002] In the existing technology, an effective way to improve the energy density of lithium-ion batteries is to develop and design thick electrodes, but thick electrodes have at least two problems. First, they are easy to break and have poor mechanical properties. Second, nano-sized positive electrode particles are difficult to disperse. Summary of the invention
[0003] Based on this, it is necessary to provide an additive that can solve the problem that thick electrodes are easy to break and the positive electrode particles are difficult to disperse.
[0004] An additive for lithium-ion batteries, the raw materials of the additive are composed of the following parts by weight:
[0005]
[0006] The first polymer is at least one of ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, ethylene-vinyl alcohol copolymer, and methyl vinyl ether-maleic anhydride linear copolymer;
[0007] The second polymer is at least one of polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile, polypyrrole, and styrene-acrylonitrile-acrylic acid copolymer;
[0008] The stabilizer is a hydrazine compound.
[0009] The additive for lithium-ion batteries provided in the present application can be used as a dispersant for the conductive agent of lithium-ion batteries. Adding the additive to the conductive agent can significantly improve the dispersion performance of the conductive agent, reduce the viscosity and fineness of the conductive agent slurry, and reduce the resistivity of the electrode.
[0010] The lithium-ion battery additive provided in the present application is applied to the positive electrode slurry process of the lithium-ion battery, and can increase the viscosity and solid content of the slurry. Due to the increase in solid content, during the process of making thick electrodes with the slurry, the first solvent evaporates less and cracking is less likely to occur, thereby improving the mechanical properties of the thick electrode. The additive can effectively promote the dispersion of the positive electrode particles. At the same time, the viscosity stability of the positive electrode slurry material is better, thereby improving the coating uniformity.
[0011] The first solvent dissolves the remaining components of the additive and has no other special functions. Any commonly used organic first solvent can be used. For example, the first solvent is one of N-methylpyrrolidone (NMP), dimethyl sulfoxide, and dimethylformamide. Preferably, the first solvent is N-methylpyrrolidone.
[0012] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.
[0013] Optionally, the raw materials of the additive are composed by weight as follows:
[0014]
[0015] Optionally, the raw materials of the additive are composed by weight as follows:
[0016]
[0017] The first polymer contains at least one non-nitrogen-containing polar functional group, the first polymer has polyethylene as the main chain, and the non-nitrogen-containing polar functional group is one of aldehyde, hydroxyl, carbonyl and acid anhydride.
[0018] The first polymer contains a polyethylene main chain and polar functional groups such as hydroxyl, carboxyl, aldehyde, carbonyl, etc. on the main chain or side chain. Under the action of the polar functional groups, the polymer can be dissolved in a first solvent such as NMP. At the same time, the polyethylene hydrophobic structure of the main chain can be adsorbed on the surface of the positive electrode active material or the conductive agent such as carbon nanotubes and carbon black, and can produce a steric hindrance in the process of positive electrode slurry or conductive agent dispersion to prevent the secondary agglomeration of the positive electrode active material or the conductive agent, thereby achieving the effect of maintaining stable viscosity and reducing slurry fineness.
[0019] Optionally, the first polymer is at least one of ethyl cellulose (e.g., Ashland N7, Ashland N10), polyvinyl alcohol (e.g., Kuraray 3-98; Kuraray 5-98; Kuraray 11-98), polyvinyl butyral (PVB, for example, Kuraray B30H; Kuraray B60H), ethylene-vinyl alcohol copolymer (e.g., Kuraray G176; Kuraray E105), and methyl vinyl ether-maleic anhydride linear copolymer (e.g., Vantellus ZeMac E60, Vantellus ZeMac E400).
[0020] Optionally, the second polymer is at least one of polyvinylpyrrolidone (PVP, for example, BASF K17, BASF K30), hydrogenated nitrile rubber (for example, ARLANXEO 4307, ZANAN ZNL3403), polyacrylonitrile (weight average molecular weight 80,000 to 100,000), polypyrrole, and styrene-acrylonitrile-acrylic acid copolymer (for example, Japan UMGS210B).
[0021] The second polymer has a nitrogen-containing polar functional group, wherein the nitrogen contains a lone pair of electrons and can form a large π bond with the carbon atoms in the lithium ion positive electrode material, has good compatibility, and can provide an alkaline environment.
[0022] The first polymer and the second polymer preferably have a weight average molecular weight of 5000-200000, and more preferably a weight average molecular weight of 5000-50000. If the molecular weight is too small, decomposition may occur during the charge and discharge process of the lithium battery, or dissolve in the electrolyte, resulting in gas production or performance degradation of the battery. If the molecular weight is too large, it will become insoluble in the solvent, or the slurry dispersion viscosity will be high, without a significant effect of reducing the viscosity.
[0023] The first polymer is dissolved in NMP, and the viscosity of the NMP solution of the first polymer with a mass fraction of 5% at 25° C. is in the range of 10-1000 mPa·s. The second polymer is dissolved in NMP, and the viscosity of the NMP solution of the second polymer with a mass fraction of 5% at 25° C. is in the range of 10-1000 mPa·s.
[0024] Optionally, the small molecule organic amine is at least one of diethylenediamine, ethanolamine, isopropanolamine, isobutanolamine, triethanolamine, anhydrous piperazine, and guanidine carbonate.
[0025] The small molecule organic amine is used to adjust the pH value and provide an alkaline environment. It has strong polarity and forms a better wrapping for the conductive agent, thereby making the conductive material more wettable and easier to disperse.
[0026] Optionally, the stabilizer is at least one of hydroxyethylhydrazine, hydrazine hydrate, and carbohydrazide. Preferably, the stabilizer is hydroxyethylhydrazine (CAS: 109-84-2). The stabilizer has a nitrogen-hydrazine structure, has strong polarity, can provide lone pairs of electrons, adsorb on the surface of positive electrode particles or carbon particles of lithium-ion batteries, increase the polarity of positive electrode particles or carbon particles, disperse the particles, and stabilize in the first solvent without secondary agglomeration.
[0027] Optionally, the raw materials of the additive are composed by weight as follows:
[0028]
[0029] Optionally, the raw materials of the additive are composed by weight as follows:
[0030]
[0031] Optionally, the raw materials of the additive are composed by weight as follows:
[0032]
[0033] Optionally, the preparation method of the additive comprises the following steps:
[0034] The small molecule organic amine, the stabilizer, the first polymer solution and the second polymer solution are uniformly mixed at a temperature below 50° C. to obtain the additive, wherein the first polymer solution and the second polymer solution are obtained by any of the following methods:
[0035] a) dividing the first solvent into two parts, wherein one part dissolves the first polymer to obtain a first polymer solution, and the other part dissolves the second polymer to obtain a second polymer solution;
[0036] b) adding the first polymer and the second polymer in any order into the same first solvent for dissolution to obtain a first polymer solution and a second polymer solution.
[0037] In the case of adding the same first solvent for dissolution, the latter polymer is added after the first polymer is fully dissolved.
[0038] Optionally, the preparation method of the additive comprises the following steps:
[0039] dissolving a first polymer in a first solvent to obtain a first polymer solution;
[0040] dissolving a second polymer in the first solvent to obtain a second polymer solution;
[0041] The small molecule organic amine, the stabilizer, the first polymer solution and the second polymer solution are uniformly mixed at a temperature below 50° C. to obtain the additive.
[0042] Since there are many different polymer options for the first polymer and the second polymer, for polymers that require high temperature dissolution (for example, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, methyl vinyl ether-maleic anhydride linear copolymer, hydrogenated nitrile rubber, polypyrrole and styrene-acrylonitrile-acrylic acid copolymer), they are dissolved at 80-100°C under nitrogen protection (the dissolution time is selected according to actual needs, for example, 4-8h). After dissolution, the temperature needs to be lowered to below 50°C before mixing with other components.
[0043] For polymers that do not require high temperature dissolution (eg, ethyl cellulose, polyvinyl pyrrolidone, polyvinyl butyral), dissolve for 0.5 to 2 hours under nitrogen protection.
[0044] The components are mixed evenly under stirring conditions for 0.5 to 2 hours.
[0045] The present application also provides an application of the additive in a conductive agent.
[0046] A conductive agent comprises: a second solvent, a conductive material and the additive, wherein the additive is added in an amount of 10-20% of the mass of the conductive material.
[0047] The second solvent may be a common solvent for conductive agents such as N-methylpyrrolidone (NMP) and dimethylformamide (DMF).
[0048] The conductive material is at least one of carbon nanotubes, graphene, carbon black, Ketjen black, and nanocarbon fibers (VGCF).
[0049] The conductive agent has a slurry scraper fineness of 10 to 15 μm.
[0050] The film resistivity of the conductive agent is 14-16 mΩ·cm.
[0051] The conductive agent has a slurry viscosity of 400 to 550 mPa·s.
[0052] The present application also provides a use of the additive in a positive electrode slurry of a lithium-ion battery.
[0053] A lithium-ion battery positive electrode slurry, the raw materials are composed of the following parts by weight:
[0054]
[0055] The second solvent is a component of the conductive agent, the third solvent is a component of the positive electrode slurry of the lithium-ion battery, the first solvent, the second solvent and the third solvent each have their own meanings, and the three can use the same solvent or different solvents.
[0056] The third solvent may be a common solvent for positive electrode slurry, such as N-methylpyrrolidone (NMP) and dimethylformamide (DMF).
[0057] The viscosity of the lithium-ion battery positive electrode slurry after being placed for 24 hours is less than 12000 mPa·s.
[0058] The viscosity of the positive electrode slurry of the lithium-ion battery after being placed for 24 hours is less than 12000 mPa·s and greater than 9000 mPa·s. Unless otherwise specified in the present application, the viscosity refers to the viscosity at 25°C.
[0059] The solid content of the lithium ion battery positive electrode slurry is greater than 65%.
[0060] The solid content of the lithium ion battery positive electrode slurry is greater than 65% and less than 70%.
[0061] Adding additives to the positive electrode slurry materials of lithium-ion batteries can effectively promote the dispersion of nano-scale lithium iron phosphate and conductive agents, and effectively reduce the viscosity of the positive electrode slurry materials. At the same viscosity level, the solid content in the positive electrode slurry can be increased by at least 6%, which can improve efficiency and reduce consumption, prevent cracking, and improve the viscosity stability of the positive electrode slurry materials, thereby improving coating uniformity.
[0062] The additive provided in this application has at least the following beneficial effects:
[0063] (1) Used as a dispersant in the dispersion process of conductive agents such as carbon nanotubes, graphene and carbon black, with the usage amount being 10% to 20% of the mass of the conductive agent, which can significantly improve the dispersion degree of the conductive agent, reduce the viscosity of the conductive agent slurry, the fineness of the conductive agent slurry and the resistivity of the conductive agent after being made into an electrode sheet;
[0064] (2) During the lithium iron phosphate positive electrode slurrying process, after adding the PVDF solution and the conductive agent, an additive is added. The amount of the additive added is 0.1-0.5% of the mass of the positive electrode lithium iron phosphate, which can significantly increase the solid content of the positive electrode slurry and reduce the viscosity of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1a The scraper fineness diagram of the additive prepared in Example 1 applied to the conductive agent;
[0066] Figure 1b The scraper fineness diagram of the additive prepared in Example 2 applied to the conductive agent;
[0067] Figure 1c The scraper fineness diagram of the additive prepared in Example 3 applied to the conductive agent;
[0068] Figure 2a The scraper fineness diagram of the additive prepared in Comparative Example 1 applied to the conductive agent;
[0069] Figure 2b The scraper fineness diagram of the additive prepared in Comparative Example 2 applied to the conductive agent;
[0070] Figure 2c This is a scraper fineness diagram of the additive prepared in Comparative Example 3 applied to the conductive agent;
[0071] Figure 3a This is a graph showing the particle size test results of the additive prepared in Example 1 when applied to a conductive agent;
[0072] Figure 3b This is a graph showing the particle size test results of the additive prepared in Example 2 when applied to a conductive agent;
[0073] Figure 3cThis is a graph showing the particle size test results of the additive prepared in Example 3 when applied to a conductive agent;
[0074] Figure 4a This is a graph showing the particle size test results of the additive prepared in Comparative Example 1 when applied to a conductive agent;
[0075] Figure 4b This is a graph showing the particle size test results of the additive prepared in Comparative Example 2 when applied to a conductive agent;
[0076] Figure 4c This is a graph showing the particle size test results of the additive prepared in Comparative Example 3 when applied to a conductive agent;
[0077] Figure 5a The electrochemical performance test diagram of the reference example;
[0078] Figure 5b This is a test diagram of the electrochemical performance of the additive prepared in Example 1 applied to the positive electrode slurry;
[0079] Figure 6 This is the AC internal resistance (ACIR) test diagram, where the horizontal axis is the number of battery packs;
[0080] Figure 7 This is a test diagram of battery voltage, where the horizontal axis is the number of battery packs;
[0081] Figure 8 This is a test diagram of DC internal resistance (DCIR), where the horizontal axis is the number of battery packs. DETAILED DESCRIPTION
[0082] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0083] In order to better describe and illustrate the embodiments of the present application, reference may be made to one or more drawings, but the additional details or examples used to describe the drawings should not be considered as limiting the scope of the invention of the present application, any of the currently described embodiments or preferred methods.
[0084] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0085] Example 1
[0086] N-methylpyrrolidone (NMP) is used as the first solvent, 56 parts (parts by weight, the same applies to other raw materials) of NMP are weighed, and 2.4 parts of ethyl cellulose (i.e., the first polymer, specifically Ashland N7, the viscosity of this brand of ethyl cellulose is 50 cPs, which is the viscosity of an 8% by mass ethyl cellulose solution in NMP at 25°C) are added to the first solvent at a temperature of 100°C and under nitrogen protection. After continuous dissolution for 2 hours, the temperature is lowered to below 50°C, and then 9.6 parts of polyvinylpyrrolidone (i.e., the second polymer, specifically BASF K10, the viscosity of this brand of polyvinylpyrrolidone is 15 cPs, which is the viscosity of an 8% by mass polyvinylpyrrolidone solution in NMP at 25°C) are added. After dissolving for 1 hour, 16 parts of isobutanolamine (i.e., a small molecule organic amine) and 16 parts of hydroxyethylhydrazine (i.e., a stabilizer) are added, the rotation speed is 1200 rpm, and stirring is performed for 1 hour to obtain an additive.
[0087] Example 2
[0088] N-methylpyrrolidone (NMP) was used as the first solvent, 56 parts of NMP were weighed (parts by weight, the same applies to other raw materials), and 9.6 parts of hydrogenated nitrile rubber (i.e., the second polymer, specifically ARLANXEO 4307, the viscosity of the hydrogenated nitrile rubber of this grade was 800 cPs, which was the viscosity of the NMP solution of 6% hydrogenated nitrile rubber at 25°C) and 1.2 parts of ethylene-vinyl alcohol copolymer (i.e., the first polymer, specifically Kuraray G176, the viscosity of the ethylene-vinyl alcohol copolymer of this grade was 100 cPs) were added to the first solvent at a temperature of 80°C and under nitrogen protection. s, the viscosity is the viscosity of the NMP solution of 3% by mass of ethylene-vinyl alcohol copolymer at 25°C), after continuing to dissolve for 2 hours, lower the temperature to below 50°C, and then add 1.2 parts of polyvinyl butyral (i.e. the first polymer, specifically Kuraray B60H, the viscosity of this brand of polyvinyl butyral is 20cPs, and the viscosity is the viscosity of the NMP solution of 3% by mass of polyvinyl butyral at 25°C), dissolve for 1 hour, then add 16 parts of isobutanolamine (i.e. small molecule organic amine) and 16 parts of hydroxyethyl hydrazine (i.e. stabilizer), rotate at 1200rmp, stir for 1 hour to obtain the additive.
[0089] Example 3
[0090] Take N-methylpyrrolidone (NMP) as the first solvent, weigh 50 parts (weight parts, other raw materials are the same) of NMP, add 15 parts of polypyrrole (i.e. the second polymer, the viscosity of polypyrrole is 100 cPs, which is the viscosity of the NMP solution of 3% polypyrrole by mass at 25°C) to the first solvent at 80°C under nitrogen protection. After dissolving for 2 hours, cool to below 50°C, then add 2 parts of polyvinyl butyral (i.e. the first polymer, specifically Kuraray B60H, the viscosity of this grade of polyvinyl butyral is 20 cPs, which is the viscosity of the NMP solution of 3% polyvinyl butyral by mass at 25°C), dissolve for 1 hour, add 16 parts of isopropanolamine (i.e. small molecule organic amine), 16 parts of hydroxyethyl hydrazine (i.e. stabilizer), rotate at 1200 rpm, stir for 1 hour, and obtain the additive.
[0091] Comparative Example 1: No polymer added
[0092] Using N-methylpyrrolidone (NMP) as a solvent, weigh 68 parts of NMP, add 16 parts of isobutanolamine and 16 parts of hydroxyethylhydrazine, and stir at a speed of 1200 rpm for 1 hour to obtain an additive.
[0093] Comparative Example 2: No organic amine or stabilizer added
[0094] Using N-methylpyrrolidone (NMP) as a solvent, weigh 72 parts of NMP, add 2.4 parts of ethyl cellulose (the same as in Example 1) to the solvent at a temperature of 100° C. under nitrogen protection, dissolve for 2 hours, then cool to below 50° C., then add 9.6 parts of polyvinylpyrrolidone (the same as in Example 1), and dissolve for 1 hour to obtain an additive.
[0095] Comparative Example 3: No stabilizer added
[0096] Taking N-methylpyrrolidone (NMP) as a solvent, weighing 56 parts of NMP, at a temperature of 100° C. and under nitrogen protection, adding 2.4 parts of ethyl cellulose (the same as in Example 1) to the solvent, dissolving for 2 hours, cooling to below 50° C., then adding 9.6 parts of polyvinylpyrrolidone (the same as in Example 1), dissolving for 1 hour, adding 32 parts of isopropanolamine, rotating at a speed of 1200 rpm, stirring for 1 hour, and obtaining an additive.
[0097] Application Example 1: Application in Conductive Agent
[0098] Weigh 89.3 parts of N-methylpyrrolidone (NMP), add 6.7 parts of additives, mix well, add 5 parts of 5-10nm multi-walled carbon nanotubes, grind and disperse, the dispersion line speed is 15m / s, after uniform dispersion, test the viscosity, scraper fineness, particle size and film resistance. The test results of applying the additives prepared in each embodiment and comparative example to the conductive agent are shown in Table 1.
[0099] Table 1
[0100]
[0101] As shown in Table 1, the viscosity of the conductive agent slurry to which the additives of Examples 1 to 3 are added is smaller than that of the conductive agent slurry to which the additives of Comparative Examples 1 to 3 are added.
[0102] The scraper fineness diagram of Examples 1 to 3 is shown in Figure 1a to Figure 1c As shown, the scraper fineness diagram of comparative examples 1 to 3 is shown in Figure 2a to Figure 2c As shown, combined with the data in the figures and Table 1, the conductive agent slurry with the additives of Examples 1 to 3 added has a smaller fineness.
[0103] As shown in Table 1, the resistivity of the conductive agent paste to which the additives of Examples 1 to 3 are added is smaller than that of the conductive agent paste to which the additives of Comparative Examples 1 to 3 are added.
[0104] The conductive agent slurry has a lower viscosity, smaller fineness, and lower resistivity, which proves that the addition of additives can greatly improve the dispersion properties of the conductive agent.
[0105] Application Example 2: Application in positive electrode slurry
[0106] The positive electrode slurry was prepared in the ratio of lithium iron phosphate: carbon black: binder PVDF: additive: NMP = 97:1:2.5:0.2:43.67. After the positive electrode slurry was prepared, the viscosity was tested at the initial stage, after 2 hours, 4 hours, 8 hours, and 24 hours. The viscosity and diaphragm resistance were tested. The results are shown in Table 2.
[0107] In Table 2, no additive was added in the reference example.
[0108] Table 2
[0109]
[0110]
[0111] The CV curve of the positive electrode slurry configured in the reference example is as follows Figure 5a As shown, the positive electrode slurry prepared by the additive configuration of Example 1 is as follows Figure 5b As shown, there is no significant difference in the electrochemical performance test between the addition of additives and the normal test without additives. The additive can remain stable and not decompose at a voltage above 4.5V, and there is no obvious redox peak, which means that the additive is stable in the battery, has no side reactions, and can be used in high voltage systems.
[0112] As shown in Table 2, after adding the additives prepared in each embodiment, the viscosity of the positive electrode slurry is significantly reduced, and the resistivity of the membrane is slightly reduced, indicating that the viscosity of the positive electrode slurry can be reduced by the introduction of the additive, so the effective component content can be actually increased, the use of the third solvent can be reduced, the efficiency of the electrode baking can be improved, and thick electrodes can be made to prevent the cracking of the electrode. At the same time, the resistivity of the membrane is basically the same as that without adding additives, indicating that the introduction of additives does not affect the internal resistance of the battery. Although the additive is not conductive, it can help the positive electrode and the conductive agent to disperse, and improve the overall battery performance.
[0113] Battery test performance characterization
[0114] The positive electrode slurry was prepared according to the data shown in Table 3, and the battery cells were manufactured. The AC internal resistance, platform voltage and DC internal resistance were tested.
[0115] Table 3
[0116]
[0117]
[0118] The weight ratio of 280 lithium iron positive electrode slurry is: lithium iron phosphate: carbon black: binder PVDF: NMP = 97:1:2.5:43.67.
[0119] In Experiment 2, 0.2% of the additive prepared in Comparative Example 1 was added, that is, the amount of the additive prepared in Comparative Example 1 was 0.2% of the mass of the lithium iron phosphate. Similarly, in Experiment 3, 0.03% of the additive prepared in Example 1 was added, that is, the amount of the additive prepared in Example 1 was 0.03% of the mass of the lithium iron phosphate.
[0120] As shown in Table 3, the solid content of Experiment 3 was increased to 66.6%, and the slurry viscosity of Experiment 3 was reduced to 4010 Mpa.s.
[0121] The three positive electrode slurries prepared in Experiments 1, 2 and 3 had no obvious abnormalities such as particles and scratches during the electrode coating process, and there were no abnormal belt breaks or wrinkles during rolling.
[0122] See also Figure 6 As shown, after adding the additive prepared in Comparative Example 1 in Experiment 2, the AC internal resistance of the battery cell increased, and after adding the additive prepared in Example 1 in Experiment 3, the AC internal resistance of the battery cell decreased by more than 30%.
[0123] See also Figure 7 As shown, the voltage of the capacitance platform in Experiments 2 and 3 increased by about 5%, while the voltage of the capacitance platform in Experiment 1 was lower.
[0124] See also Figure 8As shown, after adding the additive prepared in Example 1 in Experiment 3, the DC internal resistance of the battery cell was reduced by nearly 50%.
[0125] The test results of the standard charge and discharge energy retention rates (1P / 0.5P; 2P / 0.5P) of Experiments 1, 2 and 3 are shown in Tables 4 and 5. In Experiment 3, after adding the additive prepared in Example 1, the battery 0.5P voltage platform and 2P charge energy retention rate were significantly improved.
[0126] Table 4
[0127]
[0128] Table 5
[0129]
[0130]
[0131] The test results of the standard charge and discharge energy retention rates (1P / 0.5P; 2P / 0.5P) of Experiments 1, 2 and 3 are shown in Tables 6 and 7. In Experiment 3, after adding the additive prepared in the embodiment, the battery platform voltage, 1P and 2P charge and discharge energy efficiencies were significantly improved.
[0132] Table 6
[0133]
[0134]
[0135] Table 7
[0136]
[0137]
[0138] As shown in Table 8, there is basically no difference in the high temperature charge and discharge performance of the batteries in Experiments 1, 2 and 3.
[0139] Table 8
[0140]
[0141]
[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0143] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. An additive for lithium-ion batteries, characterized in that: The raw materials weight parts of the additive are as follows: The first polymer is at least one of ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, ethylene-vinyl alcohol copolymer, and methyl vinyl ether-maleic anhydride linear copolymer; The second polymer is at least one of polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile, polypyrrole, and styrene-acrylonitrile-acrylic acid copolymer; The stabilizer is a hydrazine compound.
2. The additive for lithium ion batteries according to claim 1, characterized in that The small molecule organic amine is at least one of diethylenediamine, ethanolamine, isopropanolamine, isobutanolamine, triethanolamine, anhydrous piperazine and guanidine carbonate.
3. The additive for lithium ion batteries according to claim 1, characterized in that: The stabilizer is at least one of hydroxyethyl hydrazine, hydrazine hydrate and carbohydrazide.
4. The additive for lithium ion batteries according to claim 1, characterized in that The raw materials weight parts of the additive are as follows:
5. The additive for lithium ion batteries according to claim 1, characterized in that: The raw materials weight parts of the additive are as follows:
6. The additive for lithium ion batteries according to claim 1, characterized in that: The raw materials weight parts of the additive are as follows:
7. The additive for lithium ion batteries according to claim 1, characterized in that: The steps include: The small molecule organic amine, the stabilizer, the first polymer solution and the second polymer solution are uniformly mixed at a temperature below 50° C. to obtain the additive, wherein the first polymer solution and the second polymer solution are obtained by any of the following methods: a) dividing the first solvent into two parts, wherein one part dissolves the first polymer to obtain a first polymer solution, and the other part dissolves the second polymer to obtain a second polymer solution; b) adding the first polymer and the second polymer in any order into the same first solvent for dissolution to obtain a first polymer solution and a second polymer solution.
8. The additive for lithium ion batteries according to claim 7, characterized in that: The small molecule organic amine, the stabilizer, the first polymer solution and the second polymer solution are uniformly mixed under stirring conditions for a mixing time of 0.5 to 2 hours.
9. Use of the additive according to any one of claims 1 to 8 in a conductive agent.
10. Use of the additive according to any one of claims 1 to 8 in positive electrode slurry for lithium ion batteries.
Citation Information
Patent Citations
Lithium ion battery positive electrode slurry, preparation method thereof and lithium ion battery
CN110797536A
Lithium battery positive electrode material and preparation method thereof
CN111446438A
Anti-oxidation transparent conductive film and preparation method and application thereof
CN113744928A
Positive electrode film layer additive composition, positive electrode film layer additive, positive electrode plate and secondary battery
CN114050260A
Method for preparing positive electrode active material for lithium secondary battery and positive electrode active material prepared by method
CN116195095A
Cited By
Additive for lithium-ion battery, and use thereof
WO2025242088A1